Phytochemical and analgesic activity of root crude extracts of Dicoma niccolifera wild (Asteraceae) - C. Zimudzi,K. Rupende,S. Kativu,J. Jere and N.I. Kunonga (Journal of Applied Pharmaceutical Science, 2013)
The study aimed at evaluating the phytochemical profile and anti-nociception activity of root crude extracts of D. niccolifera, a plant commonly used to alleviate painful conditions by local communities. Standard phytochemical screening tests revealed presence of tannins, alkaloids, flavonoids, terpenoids, reducing sugars, cardiac glycosides and anthraquinones. Anti-nociception was assessed using the hot plate model on Swiss Albino mice. Mice intraperitoneally injected with root crude extract showed that the D. niccolifera root extract had analgesic activity by taking longer to react to the thermal stimulus than the control group. The extract higher doses of 500 and 1000mg/kg showed peak mean latency times of 2.39 and 2.12 seconds respectively. These latency times were found to be significantly different (p
Keywords: Dicoma niccolifera, phytochemical